Analgesic effects of astilbin partially via calcium channels through regulation on CaMKII. Issue 1 (1st January 2019) - Bi, Hui; Sun, Zhen; Chu, Qiubo; Li, Lanzhou; Guan, Xin; Zhou, Yulin; Li, Zhiwen
ABSTRACT: This study aimed to evaluate the analgesic efficacy of astilbin and its underlying mechanisms. Astilbin suppressed the symptoms of acetic acid–induced writhing, lengthened the latency period on the hot plate, and reduced the licking and biting response of formalin-injected mice, suggesting its analgesic efficacy on the central nervous system. Astilbin suppressed neuronal nitric oxide synthase and enhanced serotonin and norepinephrine in serum and brains of mice after 30 s of thermal stimulation, but it failed to influence their levels before thermal stimulation. Among six chosen antagonists, only nimodipine, a calcium channel blocker, strongly enhanced the abirritation of astilbin, as indicated by the lengthened latency period of mice treated with nimodipine plus astilbin in the hot plate test. The expression levels of c-Fos and phosphorylated calmodulin-dependent protein kinase II and c-Jun N-terminal kinase in the brains were reduced in the astilbin-treated mice. Astilbin-mediated analgesia is partially related to Ca 2+ channels.